2019
DOI: 10.1111/cch.12674
|View full text |Cite
|
Sign up to set email alerts
|

Young carers in England: Findings from the 2018 BBC survey on the prevalence and nature of caring among young people

Abstract: Background: Many young people are involved in caring for parents, siblings, or other relatives who have an illness or disability. The aim of this study was to estimate the prevalence of caring by young people in England.Method: A national survey of 925 English young people was conducted using the 18-item survey version of the Multidimensional Assessment of Caring ActivitiesChecklist for Young Carers.Results: Around 7% of young people were identified as doing at least a high amount of caring activity and 3% a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(114 citation statements)
references
References 12 publications
10
101
2
1
Order By: Relevance
“…The mixed findings between studies may be a result of different recruitment strategies, samples and measurements. It has for example been found that females are more involved in some type of caring activities, such as domestic work, than others (Joseph et al, 2019). If the findings in the current study are replicated, we need to examine why the responsibility for care lay more heavily on young adult women.…”
Section: Prevalence and Gender Differencesmentioning
confidence: 73%
“…The mixed findings between studies may be a result of different recruitment strategies, samples and measurements. It has for example been found that females are more involved in some type of caring activities, such as domestic work, than others (Joseph et al, 2019). If the findings in the current study are replicated, we need to examine why the responsibility for care lay more heavily on young adult women.…”
Section: Prevalence and Gender Differencesmentioning
confidence: 73%
“…Increasingly researchers are in need of tools that allow comparisons to be made between young carers and their peers. As such, a revised survey version of the MACA-YC18 (Joseph et al 2019) was developed to allow it to be used with all young people regardless of their caring role. The revised tool allows comparisons to be made between the everyday helping carried out by young people and those who are in a caring role.…”
Section: Ethics Of Developing the Quality Of Methodologymentioning
confidence: 99%
“…We have had personal experience of this in our own recent research in which we conducted a representative survey of 925 young carers in England (Joseph et al 2019). Our approach to this was in two stages.…”
Section: Definitional Issues That Set the Agenda For Researchmentioning
confidence: 99%
“…The estimated prevalence of young carers in Europe ranges from 4.5% among Austrian children aged 10–14 years to 8% among UK children aged 11–18 years (Leu et al, ). A recent survey from England among children aged 11–12 and 14–15 years found that 7% of children were engaging in a high amount of caring activity and 3% were engaging in a very high amount (Joseph, Kendall, et al, ).…”
Section: Introductionmentioning
confidence: 99%